Transformasi Pers Indonesia di Era Digital dan Kecerdassan Buatan : Jejak Digital dan Warisan Media Cetak - Dalimunthe, Hotmayjar Ardila; Septika, Ghina; Nabawi, Ahmad; Manurung, Afwan Syahril (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The transformation of the Indonesian press has reached a critical point with the development of digital technology and artificial intelligence (AI). This article explores the dynamics of print media digitalization, AI implementation in journalism, and collaborative efforts to preserve digital footprints as cultural heritage. Based on a review of literature and data analysis, the article finds that digitalization expands media reach but presents sustainability challenges. Meanwhile, AI supports news production efficiency but raises ethical issues. Recommendations include digital preservation strategies and cross-sector collaboration to maintain information integrity.